Metabolomic Profiling and Biological Activities of Pleurotus columbinus Quél. Cultivated on Different Agri-Food Byproducts - Paola Angelini; Roberto Maria Pellegrino; Bruno Tirillini; Giancarlo Angeles Flores; Husam B. R. Alabed; Federica Ianni; Francesca Blasi; Lina Cossignani; Roberto Venanzoni; Giustino Orlando; Luigi Menghini; Claudio Ferrante (Antibiotics, 2021)
The genus Pleurotus (Fr.) P. Kumm (Pleurotaceae, Basidiomycota) comprises a cosmopolitan group of mushrooms highly appreciated for their nutritional value and health-promoting benefits. Despite there being many studies about the phytochemical composition of Pleurotus spp., there are very few reports dealing with the phytochemistry, antioxidant and antimicrobial activities of P. columbinus Quél. In this study, a mass spectrometry ultra-performance liquid chromatography mass spectrometry (UHPLC)-QTOF method, coupled with principal component analysis (PCA), was applied to the P. columbinus metabolome in order to investigate the influence of different agri-food residues as growth substrates for P. columbinus cultivation, on the bioactive chemical profile of fruiting bodies and evaluated their potential as antioxidants and antimicrobials. Additionally, a quantitative HPLC-DAD-MS analysis was conducted on phenolic and flavonoid compounds, that could explain, albeit partially, the observed biological effects of P. columbinus extracts. The qualitative metabolic profile identified 97 metabolites, whereas the quantitative HPLC-DAD-MS analysis confirmed the presence of phenolic and flavonoids, in the mushroom extracts, which also showed intrinsic scavenging/reducing and antimicrobial effects. The antibacterial effects were particularly evident against Escherichia coli, whereas Tricophyton and Aspergillus were the dermatophytes more sensitive to the mushroom extracts. The present study supports more in-depth investigations, aimed at evaluating the influence of growth substrate on P. columbinus antimicrobial and antioxidant properties. The extracts from P. columbinus revealed valuable sources of primary and secondary metabolites, thus suggesting potential applications in the formulation of food supplements with biological properties, above all in terms of antioxidant and antimicrobial properties.